Broken Home as Inspiration in the Creative Process of Painting Art - Shafira, Tasya; Rajudin, Rajudin; Miswar, Miswar (Institut Seni Indonesia Padang Panjang, 2023)
A broken home is defined as a family condition that is not harmonious and does not function like a peaceful and prosperous family, due to frequent disturbances and conflicts that lead to arguments and ultimately divorce. The